Asymmetric Total Syntheses of Both Enantiomers of Plymuthipyranone B and Its Unnatural Analogues: Evaluation of anti-MRSA Activity and Its Chiral Discrimination - Mizuki Moriyama; Xiaoxi Liu; Yuki Enoki; Kazuaki Matsumoto; Yoo Tanabe (MDPI AG, 2021)
Chiral total syntheses of both enantiomers of the anti-MRSA active plymuthipyranone B and all of the both enantiomers of three unnatural and synthetic analogues were performed. These two pairs of four chiral compounds are composed of the same 3-acyl-5,6-dihydro-2H-pyran-2-one structure. The starting synthetic step utilized a privileged asymmetric Mukaiyama aldol addition using Ti(OiPr)4/(S)-BINOL or Ti(OiPr)4/(R)-BINOL catalysis to afford the corresponding (R)- and (S)-δ-hydroxy-β-ketoesters, respectively, with highly enantiomeric excess (>98%). Conventional lactone formation and successive EDCI-mediated C-acylation produced the desired products, (R)- and (S)-plymuthipyranones B and three (R)- and (S)- synthetic analogues, with an overall yield of 42-56% with a highly enantiomeric excess (95-99%). A bioassay of the anti-MRSA activity against ATCC 43300 and 33591 revealed that (i) the MICs of the synthetic analogues against ATCC 43300 and ATCC 33591 were between 2 and 16 and 4 and 16 μg/mL, respectively, and those of vancomycin (reference) were 1 μg/mL. (ii) The natural (S)-plymuthipyranone B exhibited significantly higher activity than the unnatural (R)-antipode against both AACCs. (iii) The natural (R)-plymuthipyranone B and (R)-undecyl synthetic analogue at the C6 position exhibited the highest activity. The present work is the first investigation of the SAR between chiral R and S forms of this chemical class.